IMPLEMENTASI KEBIJAKAN PEMBANGUNAN INFRASTRUKTUR KELURAHAN LANGENHARJO DI KABUPATEN KENDAL (Studi Kasus Kerusakan Jalan di Kelurahan Langenharjo) - Laras Endah Cahyani; Muhammad Fatchuriza; Maulida Putri Rahmawati (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2023)
This research aims to; (1) analyze and describe the implementation of road infrastructure development policies in Langenharjo Village, (2) analyze and describe the factors that hinder the implementation of road infrastructure development policies for sections 1 and sections 2 in Langenharjo Village. Development of road infrastructure in accordance with Law Number 38 of 2004 concerning Roads, District Regulation. Kendal No. 10 of 2015 concerning Roads. This study uses Edward III's theory which has four variables that greatly determine the success of a policy implementation, namely: (1) communication; (2) resources; (3) disposition and; (4) bureaucratic structure. The four variables above in the model built by Edward III are related to one another in achieving program goals and objectives. The background of this research is related to the existence of road damage which affects community activities. Research result; (1) Implementation of the road infrastructure development policy, operated after fulfilling functional and administrative feasibility, the party responsible for the PUPR Service and related agencies, all financing from the Regional Government of Kendal Regency, (2) inhibiting factors including, (1) lack of program socialization to the community, (2) there are no resources or employees who have the capacity to supervise roads, (3) the authority for road construction lies with the Public Works and Housing Agency, so if road damage occurs, they are waiting for repairs from the agency, (4) the process involved in road repairs takes a long time.